Four Switch Buck-Boost Quasi Single-Stage Inverter With Smooth Mode Transition Using Three-Mod Modulation Technique - Keskinkilic, Ebubekir; Tckgun, Burak; Tekgun, Burak (IEEE, 2024)
Quasi-single-stage inverters (QSSI) attract attention due to their simple structure and bidirectional operation capability. However, in the buck-boost DC-DC conversion stage, smooth transition, and efficient conversion cannot be achieved when the output voltage is close to the input voltage with the traditional two-mode control method. This is due to the pulse width ratio limitations, and non-idealities of the active and passive components. In this paper, a comparative analysis of the mode transition techniques in QSSIs is presented using methods available for DC/DC converters. The system efficiency and output voltage signal quality are selected as the performance metrics as they are important performance parameters in many applications. A 2kW QSSI is controlled using single-mode, two-mode, and three-mode modulation techniques. Simulation and experimental studies are conducted for validation. Based on these studies, it is concluded that the single-mode modulation technique performed the best in eliminating dead zone effects and reducing total harmonic distortion (THD), whereas the two-mode modulation technique achieved the highest system efficiency. The three-mode modulation has superior performance on dead zone elimination compared to the two-mode modulation and better system efficiency than the single-mode modulation method. Experimental results indicate that the three-mode modulation achieved an efficiency of 91.12% with a THD of 3.73%.
Keywords: Quasi-Single-Stage Inverter; Four-Switch Buck-Boost Converter; Dead Zone Elimination